Effectiveness of Family-Centered Empowerment Model on Psychological Improvement of Patients With Myocardial Infarction: A Bayesian Multivariate Approach - Raei, Mehdi; Ghasemi, Mohammad; Hushmandi, Kiavash; Shirmohammadi-Khoram, Nasrin; Omolbanin Seyedrezaei, Seyedeh; Rostami, Hosein; Vahedian-Azimi, Amir (Frontiers in Public Health, 2022)
Objective: There is a limited understanding of the impact of family-centered empowerment model (FCEM) on the psychological symptoms in post myocardial infarction (MI). This study aimed to evaluate the effectiveness of the family-centered empowerment model on the psychological improvement for patients with MI. Methods: The present study was a randomized controlled trial (RCT) where patients experienced a standard home cardiac rehabilitation (CR) or CR utilizing the FCEM approach. The empowerment of patients was estimated during nine assessments including pre and post intervention. Factors like quality of life (QoL), state and trait anxiety, and perceived stress were evaluated. A Bayesian multivariate mixed-effects model was used to simultaneously investigate the effect of the intervention group on study outcomes across the time. Results: Among all the participants in this study, 24 (34.3%) were female with a total mean ± standard deviation of 61.40±12.83 and 24.87±3.80 for age and BMI. The participants who were in the FCEM group, had a significant higher mean level of perceived stress (β=28.80), state anxiety (β=16.20), trait anxiety (β=3.65), physical (β=38.54), and mental quality of life (β=42.14). Moreover, the individuals in the FCEM group, had a significant higher mean level of general health (β=31.64) in the physical dimension of QoL, vitality (β=15.04), mental role limitation (β=21.84), and mental health (β=18.16) in the mental dimension of QoL.